ESCO companies in Northwest Russia legal issues and organizational schemes - Dmitri Efremov (The Research Institute of the Finnish Economy (ETLA), 2004)
Energy saving activities in accordance with ESCO (Energy Service COmpany) model is a rather new matter for Russia. Since the end of the 1990s, number of legislative acts on energy saving have been growing. However, there is still much to be done in the legislative system in order to enforce effective law environment for ESCO model operations. In order to deal with energy equipment a company needs a license for operations of electric and heat networks. This is a possible hinder for market entry for ESCO company. The possible contracting relations in the framework of Russian legislation do not perfectly fit the needs of energy saving companies. As a result, relations between ESCO and a client should rely mainly on typical contractor and sub-contractor agreements, such as consultancy/services agreements (energy auditing, organization of financing, etc.), vendor contracts, and leasing agreements. Leasing schemes seem to be very promising for ESCO projects. The costs related to equipment lease are included in the prime cost for the client and this allows for decreasing of the profit tax. For the moment, several pilot projects of ESCO have been implemented in Russia. These projects were mostly initiated with the assistance of foreign organizations and financial institutions. A small number of local ESCO companies operating in Russia mostly cannot provide turnkey well-developed energy saving offers that became a standard for foreign players. Freakish low energy and energy raw material prices are hinders for energy saving. On-going steady increase in energy tariffs and forecasted substantial tariffs growth in the medium- to long-term due to the energy reforms and possible WTO accession will create increasing incentives for companies and municipalities to save more energy. – Energy ; Conservation ; ESCO ; Russia – – Energiansäätö ESCO-konseptin (Energy Service COmpany) avulla on vielä suhteellisen uusi asia Venäjällä. 1990 luvun loppupuolella säädettiin useita lakeja, joilla pyritään edistämään energiansäästöä. Käytännössä nämä lait eivät kuitenkaan ole tukeneet energiansäästöä. Jos yhtiö Venäjällä omistaa tai operoi energian tuotannon tai siirron laitteita tai merkittävästi energiaa käyttäviä koneita ja laitteita, se katsotaan energiaverkossa toimivaksi yhtiöksi, jolloin se tarvitsee luvan operointiin sähkö- ja lämpöverkossa. Tämä nostaa ESCO-yrityksen markkinoille tulon kynnystä. Myös ESCO-yrityksen määrittelevä lainsäädäntö puuttuu. Niinpä toimintaa on harjoitettava noudattamalla muita sääntöjä kuten konsultti-, rahoitus- tai palvelu- (esim. energia-auditointi), myynti- tai leasingtoiminnan sääntöjä. Leasing sisältää merkittäviä etuja, esim. kaikki leasing-kulut voidaan vähentää verotuksessa. Venäjällä on toteutettu useita ESCO-koeprojekteja. Useimmat on toteutettu ulkomaisten organisaatioiden ja rahoituslaitosten avulla ja aloitteesta. Venäläisiä ESCO-yrityksiä on vähän, eivätkä ne pysty tarjoamaan kaikkia ESCO-palveluita. Energian ja energiaraaka-aineiden edulliset hinnat eivät luo kiihokkeita energiansäästöön. Ne nousevat kuitenkin jatkuvasti luoden markkinoita ESCO-toiminnalle. – Energia ; säästö ; ESCO ; Venäjä
Keywords: 330; Energiesparen; Unternehmen; Russland (Nordwest)